Black Beauty - Kliros, Thea; Sewell, Anna, 1820-1878. (Ashland, Ohio : Landoll's, 1993)
A horse in nineteenth-century England recounts his experiences with both good and bad masters.
"This Dover edition, first published in 1993, is a new abridgement of Black Beauty (first publication: Jarrold & Sons, London, 1877). The illustrations and introductory note have been specially prepared for this edition."--verso t.p.
Keywords: Horses -- Juvenile fiction; Horses -- Fiction